Does Financial Development Really Improve Environmental Quality in Al-Jouf Region? Empirical Contribution to the Environmental Politics - Gheraia, Zouheyr; Saadaoui, Sawssan; Abdelli, Hanane; Almawishir, Naeimah Fahad S.; Abaalkaif, Naif Nadi (International Journal of Energy Economics and Policy, 2023)
This study examines the dynamic impact of financial development, trade openness, and economic growth on carbon dioxide (CO₂) emissions in Saudi Arabia. We applied the autoregressive distributed lag bound testing technique for the period of 1990–2019. The empirical results show a long-run cointegration relationship among the variables. The long-run estimation results, however, reveal that, economic growth, and trade openness have a positive and significant impact on carbon dioxide emissions, whereas all variables have a negative and significant impact on carbon dioxide emissions, in the short-run. The findings suggest that the government should emphasize programs and policies that reduce carbon dioxide emissions by opening the trade sector, considering the roles that openness plays in reducing environmental degradation in the country, which directly enhances environmental quality.